Rapid route design of AZD7594. Issue 9 (11th June 2019) - Carter, Holly L.; Connor, Amand W.; Hart, Richard; McCabe, James; McIntyre, Allyson C.; McMillan, Angus E.; Monks, Natalie R.; Mullen, Alexander K.; Ronson, Thomas O.; Steven, Alan; Tomasi, Simone; Yates, Simon D.
Abstract : Multidisciplinary collaboration enables the rapid and efficient design and selection of an improved manufacturing route to a new potential medicine for the treatment of asthma. Abstract : A wide variety of technology platforms were used to rapidly select a commercial manufacturing route to the inhaled glucocorticoid receptor modulator AZD7594. This collaborative approach to the route design employed idea generation, high-throughput salt formation, solubility and chemical reaction screening, process analytical techniques and factorial experimental design to propose, assess and select the new strategic route within a five-month window. The selected route is currently undergoing further process development and optimisation and will be implemented in future manufacturing campaigns to supply drug substance for ongoing clinical studies and ultimately for the commercially marketed product.